Transcriptomic, Proteomic, and Functional Assays Underline the Dual Role of Extrapallial Hemocytes in Immunity and Biomineralization in the Hard Clam Mercenaria mercenaria - Schwaner, Caroline; Farhat, Sarah; Haley, John; Pales Espinosa, Emmanuelle; Allam, Bassem (Frontiers in Immunology, 2022)
Circulating hemocytes in the hemolymph represent the backbone of innate immunity in bivalves. Hemocytes are also found in the extrapallial fluid (EPF), the space delimited between the shell and the mantle, which is the site of shell biomineralization. This study investigated the transcriptome, proteome, and function of EPF and hemolymph in the hard clam Mercenaria mercenaria. Total and differential hemocyte counts were similar between EPF and hemolymph. Overexpressed genes in the EPF were found to have domains previously identified as being part of the “biomineralization toolkit” and involved in bivalve shell formation. Biomineralization related genes included chitin-metabolism genes, carbonic anhydrase, perlucin, and insoluble shell matrix protein genes. Overexpressed genes in the EPF encoded proteins present at higher abundances in the EPF proteome, specifically those related to shell formation such as carbonic anhydrase and insoluble shell matrix proteins. Genes coding for bicarbonate and ion transporters were also overexpressed, suggesting that EPF hemocytes are involved in regulating the availability of ions critical for biomineralization. Functional assays also showed that Ca2+ content of hemocytes in the EPF were significantly higher than those in hemolymph, supporting the idea that hemocytes serve as a source of Ca2+ during biomineralization. Overexpressed genes and proteins also contained domains such as C1q that have dual functions in biomineralization and immune response. The percent of phagocytic granulocytes was not significantly different between EPF and hemolymph. Together, these findings suggest that hemocytes in EPF play a central role in both biomineralization and immunity.